UJI KELAYAKAN SEDIAAN TEBAL TANPA HEMOLISIS UNTUK DIAGNOSIS Plasmodium falciparum di LABORATORIUM AKADEMI ANALIS KESEHATAN 17 AGUSTUS 1945 SEMARANG - Kusumawati, Dyah; Fiscarina, Ika Theresia (Media Farmasi Indonesia, 2018)
Background: The case of malaria in the eastern part of Indonesia requires considerable consideration in the process of making thick blood stocks. The current procedure, use hemolysis techniques. The process of removal in the malaria survey takes longer time before the preparation can be examined. The thickness of different thick blood sections causes the time for the release varies. A new microscopic observation can show whether a thick dosage without hemolysis is feasible to be used as a support for malaria diagnosis which is a gold standard. Eligibility includes the core of old violet blood cells, usually not visible granules, only eosinophil granules. Platelets are mauve and often in groups. Parasites appear small, cytoplasmic boundaries are often unreal. Ring shape often appears as "coma," "exclamation point", or "flying bird" especially in Plasmodium falciparum. Method : This research is experimental because experimentation of thick blood supply of malaria that is dihemolisis and without hemolysis then done comparison on result of microscopic picture of blood thickness malaria.Primary data were obtained from the dyeing quality of thick blood samples with hemolysis techniques and without hemolysis were assessed by score. To determine whether the thick blood preparations included preparations of good or suitable staining qualities were used for the diagnosis of malaria, a normality test was performed using Kolmogorov smirnov. Furthermore, if the data is normally distributed using the T test, if the data is not normally distributed using alternative test Wilcoxon.Result : result of examination on the test of the feasibility of blood thickness of malaria with hemolysis technique and without hemolysis obtained thick blood stock with hemolysis technique as much as 20 stocks, 20% bad category, 80% good category. While without hemolysis 5% category less good, 95% good category. The result of difference test of sig value is 0.565> α 0.05 hence there is no difference of result of microscopic image assessment of thickness of malaria between hemolysis and without hemolysis.Conclusion :. There was no significant difference between the observed thick dosage forms of hemolysis techniques with no hemolysis (from observation: Plasmodium Cytoplasm, Plasmodium Core and Background of the Stock) so that thick preparations without hemolysis are feasible for the diagnosis of malaria.